If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 1a = 2 Solving 1 + 1a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 1a = 2 + -1 Combine like terms: 1 + -1 = 0 0 + 1a = 2 + -1 1a = 2 + -1 Combine like terms: 2 + -1 = 1 1a = 1 Divide each side by '1'. a = 1 Simplifying a = 1
| 4x+7+y=22 | | 25a^2-49= | | x^2+11x=36 | | 6y-5x=12fory | | 3(x+1)=8(x-2)+6 | | 36x^3+3x^2-18x= | | 2x^2-18xy-5x+45y= | | 2(4x+5)=17 | | 10m-28=72 | | 5+5x=-7+x | | 24xy-20by+18x-15b= | | 3x^2+9x-2x-6= | | a+7b+a+3c= | | (4x+1)(4x+1)=(3x-1)(3x-1) | | 36x+12x^2-12xy= | | 4x-5y+9+2x-y-14= | | 2x(x^4+6x^3+8x^2-6x-9)=0 | | 10(s-4)=-119 | | 15x^2+26x+8= | | 8+k=3 | | 3(2)(2)+2= | | C/20-42=59 | | x+x(x+1)+(x+2)=24 | | 8x+8y=-16 | | 12.9+-2.2= | | 6x-6=4x+34 | | 12ax-y+2ay-6x= | | -8(2a+5)-4= | | 13.7+-0.1+-2.4= | | -3(-5p+8)-p= | | 2+7y=11-y-y | | 5x(5x+2)-(5x+2)= |